Plasma biomarkers of clinical response during chemotherapy plus combination antiretroviral therapy (cART) in HIV+ patients with advanced Kaposi sarcoma - Tedeschi, Rosamaria (Oncotarget, 2015)
This study aimed to evaluate plasma concentration of selected cancer-associated inflammatory and immune-modulated cytokines in HIV+ patients with advanced Kaposi sarcoma (KS), and to explore candidate biomarkers capable of predicting clinical outcome in response to chemotherapy (CT) plus combination antiretroviral therapy (cART). Thirty-seven plasma cytokines/chemokines were assessed by Luminex technology in 27 consecutive HIV+ KS patients, followed-up during CT and cART of maintanence (m-cART). Associations between plasma concentration of biomarkers and patient clinical response to m-cART were evaluated by means of Hazard Ratios (HRs) and corresponding 95% Confidence Intervals (CIs). Plasma baseline concentration of Granulocyte colony-stimulating factor (G-CSF), Hepatocyte growth factor (HGF) and endoglin were found to be associated with m-cART clinical response (HR:1.56, 95%CI:1.09–2.22, p = 0.01; HR:0.32, 95% CI:0.10–0.99, p = 0.05; HR:0.72, 95% CI:0.54–0.96, p = 0.03, respectively). The multivariate analysis confirmed the associations of baseline plasma G-CSF and HGF concentration with m-cART clinical complete remission response (HR:1.78, 95% CI:1.15–2.74, p = 0.009; HR:0.19, 95% CI:0.04–0.95, p = 0.04). Our exploratory study suggested that plasma G-CSF, HGF and endoglin may be novel predictors of clinical response during m-cART in HIV+ KS patients. Nonetheless, these findings should be further validated in an independent population study.